A Janus 3D DNA nanomachine for simultaneous and sensitive fluorescence detection and imaging of dual microRNAs in cancer cells. Issue 32 (31st July 2020) - Yang, Zezhou; Peng, Xin; Yang, Peng; Zhuo, Ying; Chai, Ya-Qin; Liang, Wenbin; Yuan, Ruo
Abstract : A Janus three-dimensional DNA nanomachine was constructed for the simultaneous and sensitive fluorescent detection and imaging of dual microRNAs in the cancer cells. Abstract : Herein, a Janus three-dimensional (3D) DNA nanomachine was constructed for the simultaneous and sensitive fluorescence detection and imaging of dual microRNAs (miRNAs) in cancer cells, which could effectively eliminate signal interference in a homogeneous nanoparticle-based 3D DNA nanostructure caused by the proximity of the two different signal probes to achieve accurate co-location in the same position of living cancer cells. In this system, the Janus nanoparticles were synthesized as the carrier for immobilizing two different oligonucleotides on two different functionalized hemispheres of the nanoparticles to form a Janus 3D DNA nanostructure, which could convert trace amounts of miRNA-21 and miRNA-155 targets into massive FAM and Cy5-labeled duplexes to induce two remarkable fluorescence emissions by the catalytic hairpin assembly (CHA) and 3D DNA walker cascade nucleic acid amplification strategy, realizing sensitive detection and imaging of miRNA targets in cancer cells. Impressively, in comparison with current miRNA imaging methods based on nanoparticle assemblies, the proposed strategy could efficiently eliminate "false positive" results obtained in single type miRNA detection and distinctly increase the immobilization concentration of two different signal probes using Janus nanoparticles as the carrier to further enhance fluorescence intensity, resulting in accurate co-location in the same position of living cells. Meanwhile, the proposed fluorescence imaging technology makes it possible to visualize low concentrations of miRNAs with tiny change associated with some cancers, which could significantly improve the accuracy and precision compared to those of the conventional fluorescence in situ hybridization (FISH) approach. Therefore, it could serve as persuasive evidence for supplying accurate information to better understand biological processes and investigate mechanisms of various biomolecules and subcellular organelles, resulting in the further validation of their function in tumor proliferation and differentiation. This strategy provided an innovative approach to design new generations of nanomachines with ultimate applications in bioanalysis and clinical diagnoses.